DAKWAH MELALUI DUNIA MAYA (INTERNET) - Hamiruddin, Hamiruddin (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2020)
The presence of the internet as the most complete and efficient communication media has a wide influence in people's lives. All messages can easily be received and have become a part of people's lives. As information technology advances, propaganda material can be found everywhere. Therefore, mastery of the internet is a must for perpetrators of da'wah for the sake of efficiency and effective implementation of da'wah. Using the internet as a strategic and appropriate way to convey the teachings of Allah Almighty. The use of the internet as a da'wah media is innovation and opportunity as well as a challenge to broaden the horizon of da'wah. Thus, as perpetrators of da'wah must be challenged to master and be able to take advantage of the existence of the internet, because from the da'wah side the power of the internet is very potential to be utilized in the implementation of da'wah today.